Health Concept and Knowledge Management: Twenty-five Years of Evolution - Cornet, R.; Chute, C. G. (Yearbook of Medical Informatics, 2016)
Objectives: The fields of health terminology, classification, ontology, and related information models have evolved dramatically over the past 25 years. Our objective was to review notable trends, described emerging or enabling technologies, and highlight major terminology systems during the interval.Methods: We review the progression in health terminology systems informed by our own experiences as part of the community involved in this work, reinforced with literature review and citation.Results: The transformation in size, scope, complexity, and adoption of health terminological systems and information models has been tremendous, on the scale of orders of magnitude.Conclusion: The present “big science” era of inference and discovery in biomedicine would not have been possible or scalable absent the growth and maturation of health terminology systems and information models over the past 25 years.
Keywords: Terminology; classification; ontology; information model